From COVID-19 Pandemic to Patient Safety: A New “Spring” for Telemedicine or a Boomerang Effect? - De Micco, Francesco; Fineschi, Vittorio; Banfi, Giuseppe; Frati, Paola; Oliva, Antonio; Travaini, Guido Vittorio; Picozzi, Mario; Curcio, Giuseppe; Pecchia, Leandro; Petitti, Tommasangelo; Alloni, Rossana; Rosati, Enrico; et al. (Frontiers in Medicine, 2022)
During the Covid-19 health emergency, telemedicine was an essential asset through which health systems strengthened their response during the critical phase of the pandemic. According to the post-pandemic economic reform plans of many countries, telemedicine will not be limited to a tool for responding to an emergency condition, but it will become a structural resource that will contribute to the reorganization of Healthcare Systems and enable the transfer of part of health care from the hospital to the home-based care. However, scientific evidence has shown that health care delivered through telemedicine can be burdened by numerous ethical and legal issues. Although there is an emerging discussion on patient safety issues related to the use of telemedicine, there is a lack of research specifically designed to investigate patient safety. On the contrary, it would be necessary to determine standards and specific application rules in order to ensure safety. This paper examines the telemedicine-risk profiles and proposes a position statement for clinical risk management to support continuous improvement in the safety of health care delivered through telemedicine.